The multi-point hydraulic control method for advanced controller design of the open canal irrigation systems. Issue 2 (14th March 2023) - Zhu, Zheli; Guan, Guanghua; Wang, Kang
Abstract: Most studies about the automatic control of open canal irrigation systems only focus on the distant downstream water level, which ignores the fact that the offtakes may be located anywhere along the canal. Such a simplified control strategy is likely to result in uncontrollable and inefficient water delivery. Therefore, a multi-point hydraulic control method is proposed, in which a simplified Saint-Venant model is formulated to describe the hydraulic states of multiple controlled points. Then, it is underlined that the controlled points with and without the offtakes may have different control objectives. It is suggested to implement soft constraints to the downstream end when there is no offtake, meaning that moderate water level fluctuations are acceptable. By comparing with the common model predictive control (MPC) controller, where the Integrator Delay model and hard constraint are used for distant downstream water level control, the proposed MPC controller successfully improved the water level control stability before the offtakes and the water supply reliability by 91 and 69.5% under the conventional condition and by 54.9 and 27.1% under the water-deficient condition. Accordingly, the proposed multi-point hydraulic control method shows great potential for the precision irrigation of large irrigation districts. HIGHLIGHTS: Simplified Saint-Venant equations are formulated for the offtakes control along the irrigation canal. The differences in control objectives between various controlled points are underlined. A soft constraint is applied to the canal downstream end for operation safety. The control performance of irrigation water is remarkably enhanced with the proposed control method. Graphical Abstract